The effect of Kuiyuan chewing tablet on hyperuricemia: protocol for a randomized, double-blind, multicenter, parallel-controlled trial - Han, Man; Yao, Chuanhui; Huang, Yuting; Zhang, Jianyong; Yu, Jing; Lu, Xinliang; Xue, Yu; Tang, Xiaopo; Zou, Hejian; Jiang, Quan (Frontiers in Endocrinology, 2025)
BackgroundHyperuricemia (HUA) is a metabolic disorder characterized by elevated serum uric acid levels resulting from dysfunction in purine metabolism and/or inadequate uric acid excretion. It is an independent risk factor for many chronic diseases and is associated with a poor long-term prognosis. Existing uric acid-lowering drugs often lead to numerous adverse reactions, resulting in poor patient compliance and limited clinical application. Therefore, this study aims to investigate the effect of Kuiyuan Chewing Tablet (KYCT) on serum uric acid (SUA) levels in patients with HUA, and to seek a safe alternative therapy for reducing uric acid.Methods and analysisThis study is a multicenter, randomized, double-blind, parallel-controlled trial. HUA patients who meet the inclusion criteria will be randomly assigned in a 1:1 ratio to either (1) the control group (placebo of KYCT, specifications: 0.3g per tablet, 1.2g per dose, twice a day, taken with warm water 30 minutes after meals) or (2) the experimental group (KYCT, specifications: 0.3g per tablet, 1.2g per dose, twice a day, taken with warm water 30 minutes after meals). Both groups will receive dietary control, comorbidity prevention, and health education during the intervention period. The primary outcome will be the proportion of subjects with SUA levels <420 umol/L. Secondary outcomes will include the proportion of subjects with SUA levels <360 umol/L, the percentage change in SUA levels from baseline to each visit, the maximum percentage change in SUA levels from baseline to the third month, the number of gout attacks, changes in body measurements (weight, waist circumference, hip circumference, BMI), blood pressure, blood lipids, fasting blood glucose levels, and the proportion of subjects reporting gout attacks (cumulative up to each visit). Each group of patients will be assessed at baseline, as well as at the 4th, 8th, and 12th weeks.DiscussionThis study aims to evaluate the effects of a 12-week treatment with KYCT on patients with HUA. We hypothesize that compared to placebo, KYCT would significantly improve SUA levels without provoking significant adverse reactions. These findings potentially pave the way for a safe and effective alternative therapy for HUA.